When nobody was watching : my hard-fought journey to the top of the soccer world - Lloyd, Carli, 1982-; Coffey, Wayne R. (Houghton Mifflin Harcourt, 2016)
"The celebrated star of the U.S. women's national soccer team chronicles her amazing journey to the top,"--NoveList.